A kind of electric-transmitted anti-adhesive tape and its preparation method and application

By using porous carbon and nanosilver particles in the energized adhesive tape to improve the conductivity and improving the optical and electrical capabilities through manganese doping of nano zinc sulfide, the problem of insufficient adhesion and conductivity of existing tapes is solved, achieving more efficient battery disassembly and longer service life.

CN119193019BActive Publication Date: 2025-03-14KUNSHAN BYE MACROMOLECULE MATERIAL CO LTD

Patent Information

Application Number
CN202411751686.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing power-on-reducing adhesive tape has poor tensile strength and adhesion, which is easy to crack or break, which increases the risk of residual glue and affects the disassembly quality and efficiency of the battery; adding inorganic conductive fillers to the glue can give the glue excellent conductive properties, but they are easy to agglomerate, affecting the conductive properties of the glue, causing the glue to remain between the battery and the body.

Method used

Porous carbon is synthesized on the surface of pretreated zinc oxide whiskers to form nanosilver particles to improve conductivity and heat dissipation performance; by inducing medium gap level manganese ions in nanocrystals of nanocrystals, forming manganese-doped nanozinc sulfide, improving optical and electrical capabilities; embedded modified zinc oxide whiskers and modified manganese-doped nanozinc sulfide into cross-linking network hydrogels to avoid agglomeration and improve conductive luminescence performance.

Benefits of technology

The tensile strength and adhesion of the power-on-adhesive tape are improved, the risk of residual glue is reduced, and the quality and efficiency of battery disassembly is improved. At the same time, the heat dissipation performance of the tape is enhanced and the service life of the battery pack is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a kind of energized anti-viscosity tape and its preparation method and application, belonging to the technical field of UV tape processing for battery, and the preparation method comprises the following steps: acrylate pressure-sensitive adhesive, UV prepolymer, composite conductive hydrogel, curing agent, photoinitiator, solvent, leveling agent are mixed, stirred, and conductive glue is obtained; the conductive glue is coated on the upper and lower surfaces of aluminum foil substrate, dried at 80-100°C for 5-6min, and conductive adhesive layer is obtained, and release film is attached to the upper and lower surfaces of conductive adhesive layer to obtain energized anti-viscosity tape. The synthesized porous carbon has high porosity, which promotes manganese-doped nano zinc sulfide to emit light to initiate polymerization, cross-linking and curing of conductive adhesive layer, so that conductive adhesive layer loses viscosity; nano silver particles are formed on the surface of zinc oxide whisker loaded with porous carbon, the pore structure of porous carbon is refined, and the heat dissipation performance of energized anti-viscosity tape is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of UV tape processing for batteries, in particular to an energized de-viscosity tape and a preparation method and application thereof. Background Art

[0002] In the field of portable smart electronic appliances, in order to safely fix the device batteries, more and more electronic devices such as smart phones and tablets are bonding and fixing the batteries to the motherboard. At the same time, it makes it difficult to remove the batteries during the maintenance and recycling of the equipment. Whether the fixed batteries can be easily removed affects the development of electronic devices; the power-on de-sticking tape includes conductive glue, substrate, and release film. It is a tape that easily loses its adhesiveness after being powered on. It has high bonding strength and tensile strength before being powered on. During the replacement and maintenance process of the battery, it can be effectively thermally de-sticked after being powered on, which is convenient and quick; the power-on de-sticking tape has controllable adhesion, and the tape can be easily removed from the battery pack or vehicle parts during disassembly without causing damage. It is used to fix the battery pack of electric vehicles and has high economic benefits.

[0003] The existing power-on de-sticking tape has poor tensile strength and adhesion, and is easy to crack or break, increasing the risk of residual glue, affecting the quality and efficiency of battery disassembly; adding inorganic conductive fillers to the glue can give the glue excellent conductive properties, which is conducive to the de-sticking of the glue after power is applied, which is convenient and quick, but the inorganic conductive fillers are easy to agglomerate, affecting the conductive properties of the glue, and incomplete peeling will cause glue to remain between the battery and the body, affecting the quality and efficiency of battery disassembly. Summary of the invention

[0004] The purpose of the present invention is to provide an electrically conductive adhesive tape and a preparation method and application thereof: porous carbon is synthesized on the surface of a pretreated zinc oxide whisker, the synthesized porous carbon has a high porosity, increases the conductive channel, has good conductive performance, promotes the modified manganese-doped nano zinc sulfide to emit light, triggers the polymerization, cross-linking and curing of the conductive adhesive layer, and makes the conductive adhesive layer lose its viscosity; nano silver particles are formed in the pores of the porous carbon on the surface of the zinc oxide whisker loaded with porous carbon, refines the pore structure of the porous carbon, and improves the heat dissipation performance of the electrically conductive adhesive tape; nano zinc sulfide is mixed with manganese chloride to form manganese-doped nano Zinc sulfide, by inducing medium-gap energy level manganese ions in nano-crystals of nano-zinc sulfide, makes manganese-doped nano-zinc sulfide have good optical and electrical capabilities, which is beneficial to the effect of reducing viscosity when powered on; modified zinc oxide whiskers, modified manganese-doped nano-zinc sulfide, carboxymethyl cellulose, and acrylic acid are mixed to form a cross-linked network hydrogel, and the modified manganese-doped nano-zinc sulfide and modified zinc oxide whiskers are embedded in the cross-linked network hydrogel to avoid the modified zinc oxide whiskers and modified manganese-doped nano-zinc sulfide from being easily agglomerated when added to the glue, affecting the conductive and luminescent properties, resulting in a decrease in the viscosity-reducing properties when powered on.

[0005] The technical problem to be solved by the present invention is as follows: the existing power-on de-sticking tape has poor tensile strength and adhesion, is easy to crack or break, increases the risk of residual glue, and affects the quality and efficiency of battery disassembly; adding inorganic conductive fillers to the glue can give the glue excellent conductive properties, which is conducive to the de-sticking of the glue after power is applied, which is convenient and quick, but the inorganic conductive fillers are easy to agglomerate, affecting the conductive properties of the glue, and incomplete peeling causes glue to remain between the battery and the body, affecting the quality and efficiency of battery disassembly.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing an electrically conductive adhesive tape comprises the following steps:

[0008] S1. Mix and stir the acrylic pressure-sensitive adhesive, UV prepolymer, composite conductive hydrogel, curing agent, photoinitiator, solvent and leveling agent to obtain conductive glue.

[0009] S2. Apply conductive glue to the upper and lower surfaces of the aluminum foil substrate, dry at 80-100°C for 5-6 minutes to obtain a conductive adhesive layer, and attach a release film to the upper and lower surfaces of the conductive adhesive layer to obtain an electrically conductive anti-sticking tape.

[0010] Furthermore, the thickness of the aluminum foil substrate is 10-15 μm.

[0011] Furthermore, the release film is a polyethylene terephthalate release film with a thickness of 20-30 μm.

[0012] Furthermore, the molecular weight of the acrylic pressure-sensitive adhesive is 380,000-680,000, and the molecular weight distribution is 2.1-2.3.

[0013] Furthermore, the UV prepolymer is any one of polyurethane (meth) acrylate, polyester (meth) acrylate and polyether (meth) acrylate.

[0014] Furthermore, the curing agent is selected from any one of toluene diisocyanate, diphenylmethane diisocyanate, and isophorone diisocyanate; and the solvent is selected from ethyl acetate or cyclohexane.

[0015] Furthermore, the solvent is selected from ethyl acetate or cyclohexane.

[0016] Furthermore, the photoinitiator is selected from any one of 2-isopropylthioxanthone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and trimethylbenzoyl-diphenylphosphine oxide.

[0017] Furthermore, the leveling agent is selected from any one of leveling agent BYK358N, leveling agent BYK-333, and leveling agent BYK381.

[0018] Furthermore, the mass ratio of acrylate pressure-sensitive adhesive, UV prepolymer, composite conductive hydrogel, curing agent, photoinitiator, solvent and leveling agent is (70-100):(40-60):(5-10):(1-3):(6-8):(45-55):(0.1-1).

[0019] Furthermore, the composite conductive hydrogel is prepared by a mixed reaction of modified zinc oxide whiskers, modified manganese-doped nano zinc sulfide, carboxymethyl cellulose, acrylic acid, polyethylene glycol diacrylate and ammonium persulfate, and is specifically prepared by the following steps:

[0020] Carboxymethyl cellulose is added into deionized water and stirred until dissolved, acrylic acid, modified manganese-doped nano zinc sulfide, modified zinc oxide whisker, polyethylene glycol diacrylate and ammonium persulfate are added, stirred, ultrasonically treated to remove bubbles, placed in a glass mold, introduced nitrogen, allowed to stand, and taken out to obtain a composite conductive hydrogel.

[0021] Furthermore, in the above reaction process, ammonium persulfate is used as an initiator to polymerize acrylic acid monomers, and polyethylene glycol diacrylate is used as a cross-linking agent to undergo a cross-linking reaction with polyacrylic acid and carboxymethyl cellulose to form a cross-linked network hydrogel. The amino groups contained in the modified manganese-doped nano-zinc sulfide can also undergo a cross-linking reaction with polyacrylic acid and carboxymethyl cellulose, so that the modified manganese-doped nano-zinc sulfide is embedded in the cross-linked network hydrogel, giving the hydrogel permeability, increasing the cross-linking density, and improving the mechanical strength of the hydrogel. In addition, in the process of synthesizing the cross-linked network hydrogel, the modified zinc oxide whiskers are embedded in the hydrogel system, giving the hydrogel excellent conductive properties.

[0022] Furthermore, the dosage ratio of carboxymethyl cellulose, acrylic acid, modified manganese-doped nano zinc sulfide, modified zinc oxide whisker, polyethylene glycol diacrylate and ammonium persulfate is (1.1-1.3) g: (20-30) mL: (0.4-0.5) g: (0.5-0.6) g: (0.02-0.04) g: (0.1-0.2) g.

[0023] Furthermore, the modified zinc oxide whisker is prepared by mixing the pretreated zinc oxide whisker with a carbon precursor, carbonizing the mixture, and then reacting the mixture with a silver ammonia solution and a reducing agent.

[0024] Furthermore, the carbon precursor is selected from glucose or rice husk powder.

[0025] Furthermore, the carbonization temperature is 750-950° C., and the carbonization time is 2-4 h.

[0026] Furthermore, the silver ammonia solution is prepared by mixing silver nitrate, deionized water, and ammonia water in a dosage ratio of (0.5-1.5) g: (8-12) mL: (0.5-1.5) mL.

[0027] Furthermore, the concentration of ammonia water is 25.8-26.2%; and the reducing agent is glucose.

[0028] Further, the modified zinc oxide whisker is specifically prepared by the following steps:

[0029] A1. Add the pretreated zinc oxide whiskers to ethanol, add the carbon precursor, stir at 30°C for 1.5h, filter, wash, dry, place in a tube furnace, add potassium hydroxide for activation, introduce nitrogen, carbonize, cool to room temperature, take out, and obtain zinc oxide whiskers loaded with porous carbon.

[0030] A2. Mix the porous carbon-loaded zinc oxide whiskers with the silver ammonia solution, stir evenly, add a reducing agent, stir until the reducing agent is dissolved, and after the stirring reaction is completed, filter, wash, and dry to obtain modified zinc oxide whiskers.

[0031] Furthermore, in the above-mentioned A1 reaction process, the polydopamine layer contained on the surface of the pretreated zinc oxide whisker can adhere the carbon precursor to the surface of the pretreated zinc oxide whisker. After high-temperature carbonization, the carbon precursor is thermally decomposed to form a dense carbon layer, and the activator potassium hydroxide molecules are decomposed to form pores on the surface of the dense carbon layer, thereby realizing the synthesis of porous carbon on the surface of the pretreated zinc oxide whisker. The synthesized porous carbon has a high porosity, increased conductive channels, and good conductive properties.

[0032] Furthermore, during the above-mentioned A2 reaction process, the porous carbon structure on the surface of the zinc oxide whisker loaded with porous carbon has good adsorption performance, and can adsorb the silver ammonia solution into the pores of the porous carbon, so that the silver ions are adsorbed onto the surface of the zinc oxide whisker loaded with porous carbon. Glucose, as a reducing agent, can reduce the silver ions in the silver ammonia solution to silver, thereby forming nanosilver particles in the pores of the porous carbon to form modified zinc oxide whiskers.

[0033] Furthermore, in step A1, the ratio of the pretreated zinc oxide whiskers, ethanol, carbon precursor, and potassium hydroxide is (1-2) g: (35-45) mL: (4-5) g: (4-5) mL.

[0034] Furthermore, in step A2, the ratio of the zinc oxide whiskers loaded with porous carbon, the silver ammonia solution, and the reducing agent is (0.5-1.5) g: (15-25) mL: (1-3) g.

[0035] Further, the pretreated zinc oxide whiskers are specifically prepared by the following steps:

[0036] The zinc oxide whisker was added into Tris-HCl buffer, stirred evenly, dopamine was added, stirred for 3-5 hours, filtered, washed with deionized water for 3 times, and dried in an oven at 70° C. for 10 minutes to obtain the pretreated zinc oxide whisker.

[0037] Furthermore, dopamine can self-polymerize on the surface of zinc oxide whiskers to form polydopamine, which makes the zinc oxide whiskers have better adhesion and is conducive to the formation of a porous carbon structure on the surface of the zinc oxide whiskers.

[0038] Furthermore, the dosage ratio of zinc oxide whisker, Tris-HCl buffer and dopamine is (0.5-1.5) g: (45-55) mL: (0.3-0.7) g.

[0039] Furthermore, the zinc oxide whisker has a length of 5-10 μm and a diameter of 0.5-1 μm.

[0040] Furthermore, the modified manganese-doped nano zinc sulfide is prepared by mixing nano zinc sulfide and manganese chloride, calcining, and then surface-modifying with a silane coupling agent.

[0041] Furthermore, the calcination temperature is 750-850°C, and the calcination time is 2-3h.

[0042] Furthermore, the silane coupling agent is selected from γ-aminopropyltriethoxysilane.

[0043] Furthermore, the modified manganese-doped nano zinc sulfide is prepared by the following steps:

[0044] B1. Mix zinc sulfide powder, manganese chloride and sodium chloride, grind them in a grinder, place the ground mixture on the bottom of a corundum crucible, spread sodium chloride, place it in a muffle furnace, calcine, cool to room temperature, take it out, and obtain manganese-doped nano zinc sulfide.

[0045] B2. Add manganese-doped nano zinc sulfide to deionized water, stir evenly, add silane coupling agent and ethanol, stir and react at 40° C. for 5 minutes, filter, wash and dry to obtain modified manganese-doped nano zinc sulfide.

[0046] Furthermore, in the above B1 reaction process, nano zinc sulfide is mixed with manganese chloride and calcined at high temperature, so that the manganese ions in the manganese chloride partially occupy the position of zinc ions in the nano zinc sulfide crystals, thereby achieving manganese ion doping into the nano zinc sulfide lattice to form manganese-doped nano zinc sulfide.

[0047] Furthermore, in the above-mentioned B2 reaction process, the silanol groups produced by the hydrolysis of the silane coupling agent can be combined with the hydroxyl groups on the surface of the manganese-doped nano-zinc sulfide through chemical bonds, so that the silane coupling agent is grafted on the surface of the manganese-doped nano-zinc sulfide, consuming the oxygen-containing functional groups on the surface of the manganese-doped nano-zinc sulfide, and avoiding the zinc element on the surface of the manganese-doped nano-zinc sulfide from combining with oxygen to form a zinc oxide coating, which affects the luminescent performance when powered on.

[0048] Furthermore, in step B1, the mass ratio of zinc sulfide powder, manganese chloride and sodium chloride is (2-3):(0.05-0.09):(8-9).

[0049] Furthermore, in step B2, the dosage ratio of manganese-doped nano-zinc sulfide, deionized water, KH550, and ethanol is (0.4-0.5) g: (10-15) mL: (2-3) g: (20-30) mL.

[0050] Furthermore, compared with the prior art, the present invention has the following beneficial effects:

[0051] (1) In the technical scheme of the present invention, porous carbon is synthesized on the surface of pretreated zinc oxide whiskers. The synthesized porous carbon has high porosity, increases the conductive channel, and has good conductive properties, which promotes the modified manganese-doped nano-zinc sulfide to emit light and trigger the polymerization, cross-linking and curing of the conductive adhesive layer, so that the conductive adhesive layer loses its viscosity. The formed porous carbon has good heat transfer efficiency and can release the heat generated by the battery pack, thereby improving the heat dissipation performance of the battery pack and the service life of the battery pack. It also has good heat dissipation performance, which prevents the conductive adhesive tape from absorbing heat and causing thermal aging of its conductive adhesive layer, thereby affecting the adhesion strength of the conductive adhesive tape.

[0052] (2) In the technical solution of the present invention, nanosilver particles are formed in the pores of the porous carbon on the surface of the zinc oxide whisker loaded with porous carbon. On the one hand, the pore structure of the porous carbon is refined, the heat dissipation performance of the battery pack is improved, and the thermal aging performance of the energized anti-viscosity tape is further enhanced. On the other hand, the excellent adsorption performance of the porous carbon is conducive to the fixation of the nanoporous silver, avoiding the shedding of the nanosilver and causing a decrease in the conductive performance.

[0053] (3) In the technical scheme of the present invention, nano zinc sulfide is mixed with manganese chloride and calcined to form manganese-doped nano zinc sulfide. By inducing medium-gap energy level manganese ions in the nanocrystals of nano zinc sulfide, the manganese-doped nano zinc sulfide has good optical and electrical capabilities. After power is turned on, the charge generated by the modified zinc oxide whiskers enables the manganese-doped nano zinc sulfide to produce energy excitation and recombination processes, thereby emitting visible light. The generated visible light can then trigger the polymerization, cross-linking and curing of the conductive adhesive layer, causing the conductive adhesive layer to lose its viscosity, achieving the effect of reducing viscosity when powered on, and facilitating the detachability of the battery pack of the electric vehicle; the manganese-doped nano zinc sulfide is surface treated with a silane coupling agent to consume the oxygen-containing functional groups on the surface of the manganese-doped nano zinc sulfide, thereby preventing the zinc element on the surface of the manganese-doped nano zinc sulfide from combining with oxygen to form a zinc oxide coating, which affects the luminescent performance when powered on.

[0054] (4) In the technical scheme of the present invention, modified zinc oxide whiskers, modified manganese-doped nano zinc sulfide, carboxymethyl cellulose, and acrylic acid are mixed to form a cross-linked network hydrogel, and modified manganese-doped nano zinc sulfide and modified zinc oxide whiskers are embedded in the cross-linked network hydrogel to give the hydrogel permeability and excellent conductive properties, and to avoid the modified zinc oxide whiskers and modified manganese-doped nano zinc sulfide being easily agglomerated when added to the glue, affecting the conductive and luminescent properties, resulting in a decrease in the energized viscosity-reducing performance; the hydrogel with conductive and luminescent properties is added to the conductive glue to prepare the energized The anti-viscosity tape has high bonding strength and mechanical strength before power is applied, and the modified zinc oxide crystals and modified manganese-doped nano-zinc sulfide exist in the cross-linked network hydrogel, shortening the distance between the modified zinc oxide crystals and the modified manganese-doped nano-zinc sulfide. After power is applied, the excellent conductivity of the modified zinc oxide whiskers transfers the charge to the entire conductive adhesive layer. The generated charge can quickly act on the modified manganese-doped nano-zinc sulfide to emit light, thereby initiating the polymerization, cross-linking and curing of the conductive adhesive layer, causing the conductive adhesive layer to lose its viscosity in a short time, and has a high power-on anti-viscosity efficiency. DETAILED DESCRIPTION

[0055] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] The raw materials used in the embodiments of the present invention are as follows:

[0057] Tris-HCl buffer (purity 99.5%, Wuhan Desheng Biochemical Technology Co., Ltd.); glucose, silver nitrate (analytical grade); ammonia water (concentration 26.1%, purchased from Sinopharm Chemical Reagent Co., Ltd.); manganese chloride, sodium chloride (analytical grade, Shanghai Titan Technology Co., Ltd.); γ-aminopropyltriethoxysilane (purity 98.5%, Huangshan Kebery New Materials Technology Co., Ltd.); acrylic acid (Nantong Runfeng Petrochemical Co., Ltd.).

[0058] The average molecular weight of polyethylene glycol in polyethylene glycol diacrylate is 400, Jiangsu Congzhong Chemical Co., Ltd.

[0059] Carboxymethyl cellulose: viscosity 1000-1400 mPa·s, Shanghai Kanglang Biotechnology Co., Ltd.

[0060] The length of zinc oxide whiskers is 5-10μm and the diameter is 0.5-1μm, Huben New Material Technology Co., Ltd.

[0061] The molecular weight of acrylic pressure-sensitive adhesive is 450,000, and the molecular weight distribution is 2.2, Gongzhipin (Shanghai) Chemical Technology Co., Ltd.

[0062] Zinc sulfide powder: particle size is 50-100nm, Zhejiang Yamei Nano Technology Co., Ltd.

[0063] Example 1 The modified zinc oxide whisker is prepared by the following steps:

[0064] A1. Add 1 g zinc oxide whisker to 50 mL Tris-HCl buffer, stir evenly, add 0.5 g dopamine, stir for 4 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain pretreated zinc oxide whisker.

[0065] A2. Add 1.5 g of pretreated zinc oxide whiskers to 40 mL of ethanol, add 4.5 g of glucose, stir at 30 ° C for 1.5 h, filter, wash with deionized water three times, dry in a 60 ° C oven for 15 min, place in a tube furnace, add 4.5 mL of potassium hydroxide for activation, pass nitrogen, carbonize at 800 ° C for 3 h, cool to room temperature, take out, and obtain zinc oxide whiskers loaded with porous carbon.

[0066] A3. Mix 1 g of porous carbon-loaded zinc oxide whiskers with 20 mL of silver ammonia solution, stir evenly, add 2 g of glucose, stir until the reducing agent is dissolved, stir and react at 20°C for 1 hour, filter, wash with deionized water three times, and dry in an oven at 60°C for 15 minutes to obtain modified zinc oxide whiskers, wherein the silver ammonia solution is prepared by mixing silver nitrate, deionized water, and ammonia water in a dosage ratio of 1 g:10 mL:1 mL.

[0067] Comparative Example 1 The difference between this comparative example and Example 1 is that the zinc oxide whiskers loaded with porous carbon are replaced with pretreated zinc oxide whiskers, and the remaining steps and raw materials are the same as those in Example 1.

[0068] A1. Add 1 g zinc oxide whisker to 50 mL Tris-HCl buffer, stir evenly, add 0.5 g dopamine, stir for 4 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain pretreated zinc oxide whisker.

[0069] A2. Mix 1 g of pretreated zinc oxide whiskers with 20 mL of silver ammonia solution, stir evenly, add 2 g of glucose, stir until the reducing agent is dissolved, stir and react at 20°C for 1 hour, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 15 minutes to obtain modified zinc oxide whiskers, wherein the silver ammonia solution is prepared by mixing silver nitrate, deionized water, and ammonia water in a dosage ratio of 1 g:10 mL:1 mL.

[0070] Comparative Example 2 The difference between this comparative example and Example 1 is that no silver ammonia solution is added, and the remaining steps and raw materials are the same as Example 1.

[0071] A1. Add 1 g zinc oxide whisker to 50 mL Tris-HCl buffer, stir evenly, add 0.5 g dopamine, stir for 4 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain pretreated zinc oxide whisker.

[0072] A2. Add 1.5 g of pretreated zinc oxide whiskers to 40 mL of ethanol, add 4.5 g of glucose, stir at 30 ° C for 1.5 h, filter, wash with deionized water three times, dry in a 60 ° C oven for 15 min, place in a tube furnace, add 4.5 mL of potassium hydroxide for activation, pass nitrogen, carbonize at 800 ° C for 3 h, cool to room temperature, take out, and obtain modified zinc oxide whiskers.

[0073] Example 2 The modified manganese-doped nano zinc sulfide is prepared by the following steps:

[0074] B1. Mix 2.5 g zinc sulfide powder, 0.07 g manganese chloride and 2.5 g sodium chloride, grind them in a grinder for 30 min, place the ground mixture on the bottom of a corundum crucible, spread 6 g sodium chloride, place it in a muffle furnace, calcine at 800 ° C for 2.5 h, cool to room temperature, take out, and obtain manganese-doped nano zinc sulfide.

[0075] B2. Add 0.45 g of manganese-doped nano-zinc sulfide to 13 mL of deionized water, stir evenly, add 2.5 g of γ-aminopropyltriethoxysilane and 25 mL of ethanol, stir and react at 40 ° C for 5 minutes, filter, wash with deionized water 3 times, and dry in an oven at 85 ° C for 10 minutes to obtain modified manganese-doped nano-zinc sulfide.

[0076] Comparative Example 3 The difference between this comparative example and Example 2 is that manganese-doped nano-zinc sulfide is replaced by nano-zinc sulfide, and the remaining steps and raw materials are the same as those in Example 2.

[0077] 0.45 g of nano zinc sulfide was added to 13 mL of deionized water, stirred evenly, 2.5 g of γ-aminopropyltriethoxysilane and 25 mL of ethanol were added, stirred and reacted at 40° C. for 5 min, filtered, washed with deionized water 3 times, and dried in an oven at 85° C. for 10 min to obtain modified nano zinc sulfide.

[0078] Comparative Example 4 The difference between this comparative example and Example 2 is that γ-aminopropyltriethoxysilane is not added, and the remaining steps and raw materials are the same as those in Example 2.

[0079] Mix 2.5 g of zinc sulfide powder, 0.07 g of manganese chloride and 2.5 g of sodium chloride, and grind them in a grinder for 30 minutes. Place the ground mixture on the bottom of a corundum crucible, spread 6 g of sodium chloride, place it in a muffle furnace, calcine it at 800°C for 2.5 hours, cool it to room temperature, and take it out to obtain manganese-doped nano zinc sulfide.

[0080] Example 3 The composite conductive hydrogel is prepared by the following steps:

[0081] 1.2 g of carboxymethyl cellulose was added to 55 mL of deionized water and stirred until dissolved. 25 mL of acrylic acid, 0.45 g of modified manganese-doped nano-zinc sulfide prepared in Example 2, 0.55 g of modified zinc oxide whiskers prepared in Example 1, 0.03 g of polyethylene glycol diacrylate and 0.15 g of ammonium persulfate were added, and stirred for 10 min. Ultrasonic treatment was performed at 60 Hz to remove bubbles, and the mixture was placed in a glass mold. After nitrogen was introduced, the mixture was allowed to stand for 1 h and taken out to obtain a composite conductive hydrogel.

[0082] Comparative Example 5 The difference between this comparative example and Example 3 is that the modified zinc oxide whisker prepared in Example 1 is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 3.

[0083] Comparative Example 6 The difference between this comparative example and Example 3 is that the modified zinc oxide whisker prepared in Example 1 is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 3.

[0084] Comparative Example 7 The difference between this comparative example and Example 3 is that the modified manganese-doped nano zinc sulfide prepared in Example 2 is replaced by the material prepared in Comparative Example 3, and the remaining steps are synchronized with Example 4.

[0085] Comparative Example 8 The difference between this comparative example and Example 3 is that the modified manganese-doped nano zinc sulfide prepared in Example 2 is replaced by the material prepared in Comparative Example 4, and the remaining steps are synchronized with Example 3.

[0086] Embodiment 4 A method for preparing an electrically conductive adhesive tape comprises the following steps:

[0087] S1. 70 g of acrylate pressure-sensitive adhesive, 40 g of polyurethane (meth) acrylate, 5 g of the composite conductive hydrogel prepared in Example 3, 1 g of toluene diisocyanate, 6 g of 2-isopropylthioxanthone, 45 g of ethyl acetate, and 0.1 g of leveling agent BYK358N were mixed and stirred to obtain a conductive glue.

[0088] S2. Apply conductive glue on the upper and lower surfaces of the aluminum foil substrate, dry at 90°C for 6 minutes to obtain a conductive adhesive layer, and attach a release film to the upper and lower surfaces of the conductive adhesive layer to obtain an electrically conductive anti-sticking tape.

[0089] The thickness of the aluminum foil substrate is 13 μm.

[0090] The release film is a polyethylene terephthalate release film with a thickness of 25 μm.

[0091] Embodiment 5 A method for preparing an electrically conductive adhesive tape comprises the following steps:

[0092] S1. 85 g of acrylate pressure-sensitive adhesive, 50 g of polyester (meth) acrylate, 8 g of the composite conductive hydrogel prepared in Example 3, 2 g of diphenylmethane diisocyanate, 7 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 55 g of ethyl acetate, and 0.7 g of leveling agent BYK-333 were mixed and stirred to obtain a conductive glue.

[0093] S2. Apply conductive glue on the upper and lower surfaces of the aluminum foil substrate, dry at 90°C for 6 minutes to obtain a conductive adhesive layer, and attach a release film to the upper and lower surfaces of the conductive adhesive layer to obtain an electrically conductive anti-sticking tape.

[0094] The thickness of the aluminum foil substrate is 13 μm.

[0095] The release film is a polyethylene terephthalate release film with a thickness of 25 μm.

[0096] Example 6 A method for preparing an electrically conductive adhesive tape comprises the following steps:

[0097] S1. 100 g of acrylate pressure-sensitive adhesive, 60 g of polyether (meth)acrylate, 10 g of the composite conductive hydrogel prepared in Example 3, 3 g of isophorone diisocyanate, 8 g of trimethylbenzoyl-diphenylphosphine oxide, 55 g of cyclohexane, and 1 g of leveling agent BYK381 were mixed and stirred to obtain a conductive glue.

[0098] S2. Apply conductive glue on the upper and lower surfaces of the aluminum foil substrate, dry at 90°C for 6 minutes to obtain a conductive adhesive layer, and attach a release film to the upper and lower surfaces of the conductive adhesive layer to obtain an electrically conductive anti-sticking tape.

[0099] The thickness of the aluminum foil substrate is 13 μm.

[0100] The release film is a polyethylene terephthalate release film with a thickness of 25 μm.

[0101] Comparative Example 9 The difference between this comparative example and Example 5 is that the composite conductive hydrogel prepared in Example 3 is replaced by the material prepared in Comparative Example 5, and the remaining steps are synchronized with Example 5.

[0102] Comparative Example 10 The difference between this comparative example and Example 5 is that the composite conductive hydrogel prepared in Example 3 is replaced by the material prepared in Comparative Example 6, and the remaining steps are synchronized with Example 5.

[0103] Comparative Example 11 The difference between this comparative example and Example 5 is that the composite conductive hydrogel prepared in Example 3 is replaced by the material prepared in Comparative Example 7, and the remaining steps are synchronized with Example 5.

[0104] Comparative Example 12 The difference between this comparative example and Example 5 is that the composite conductive hydrogel prepared in Example 3 is replaced by the material prepared in Comparative Example 8, and the remaining steps are synchronized with Example 5.

[0105] Comparative Example 13 The difference between this comparative example and Example 5 is that the composite conductive hydrogel prepared in Example 3 is replaced by modified zinc oxide whiskers and modified manganese-doped nano zinc sulfide, and the remaining steps are synchronized with Example 5.

[0106] The performance of the energized debonding tapes prepared in Examples 4-6 and Comparative Examples 9-13 was tested;

[0107] The release film of the energized anti-sticking tape prepared above was torn off and attached to the electric vehicle battery pack. A 2kg rubber roller was used to press back and forth 3 times, and the release film on the other side was torn off. The electric vehicle battery pack was fixed on the electric vehicle and placed at 23°C for 24 hours before testing.

[0108] Peel force test before power-on: The peel force of the power-on debonding tape prepared above was tested according to GB / T2792-2014 standard.

[0109] Peel force test after power-on: The powered debonding tape attached to the electric vehicle battery pack is powered on (voltage is 30V), and the peel force of the powered debonding tape after power-on is tested in accordance with GB / T2792-2014 standard, and whether there is residual glue on the surface of the electric vehicle battery pack and record the debonding time.

[0110] Shear strength test: The shear strength of the electrically conductive adhesive tape prepared above was tested in accordance with GB / T7124-2008 standard.

[0111] Heat resistance test: A temperature-type tape holding force tester (MIDEL KJ-6012) was used to conduct a high-temperature holding force test at 100°C to evaluate the heat resistance of the powered tape.

[0112] The test results are shown in Table 1 below:

[0113]

[0114] It can be seen from the data in Table 1 that in Comparative Example 9, the zinc oxide whiskers loaded with porous carbon are replaced with modified zinc oxide whiskers prepared by zinc oxide whiskers and added to the energized de-viscosity tape, and the energized de-viscosity effect and high-temperature holding performance thereof are reduced. This may be because porous carbon is synthesized on the surface of the pretreated zinc oxide whiskers, which is beneficial to the fixation of nanoporous silver, and after power is applied, the manganese-doped nano-zinc sulfide is prompted to emit light, initiating polymerization, cross-linking and curing of the conductive adhesive layer, causing the conductive adhesive layer to lose its viscosity and release the heat generated by the battery pack, thereby improving the high-temperature holding performance. However, the surface of the pretreated zinc oxide whiskers lacks porous carbon and cannot achieve this effect. Therefore, the energized de-viscosity effect and high-temperature holding performance are reduced.

[0115] In Comparative Example 10, the modified zinc oxide whiskers prepared without the addition of silver ammonia solution were added to the energized de-viscosity tape, and its energized de-viscosity effect and high-temperature sustained adhesion performance decreased. This may be because nanosilver particles are formed in the pores of the porous carbon on the surface of the zinc oxide whiskers loaded with porous carbon, which can refine the pore structure of the porous carbon and improve the heat dissipation and conductivity of the battery pack. However, the lack of nanosilver particles formed in the pores of the porous carbon on the surface of the zinc oxide whiskers loaded with porous carbon can, on the one hand, refine the pore structure of the porous carbon, improve the heat dissipation performance of the battery pack, and further enhance the thermal aging performance of the energized de-viscosity tape, and this effect cannot be achieved. Therefore, the energized de-viscosity effect and high-temperature sustained adhesion performance are reduced.

[0116] In Comparative Example 11, manganese-doped nano-zinc sulfide is replaced with modified nano-zinc sulfide prepared by nano-zinc sulfide and added to the electrically conductive de-viscosity tape. Its electrically conductive de-viscosity effect is reduced. This may be because by inducing medium-gap energy level manganese ions in the nanocrystals of nano-zinc sulfide, visible light can be emitted. The generated visible light can then trigger the polymerization, cross-linking and curing of the conductive adhesive layer, thereby achieving the effect of electrically conductive de-viscosity. However, the modified nano-zinc sulfide lacks manganese ions and cannot achieve this effect. Therefore, the electrically conductive de-viscosity effect is reduced.

[0117] In Comparative Example 12, manganese-doped nano zinc sulfide prepared without adding γ-aminopropyltriethoxysilane was added to the electrically conductive de-viscosity tape, and its electrically conductive de-viscosity effect decreased. This may be because the manganese-doped nano zinc sulfide was surface-treated with silane coupling agent to prevent the zinc element on the surface of the manganese-doped nano zinc sulfide from combining with oxygen and affecting the luminescent performance when powered on. However, the surface of the manganese-doped nano zinc sulfide lacked γ-aminopropyltriethoxysilane and could not achieve this effect, so the electrically conductive de-viscosity effect decreased.

[0118] In Comparative Example 13, the composite conductive hydrogel prepared in Example 3 is replaced with modified zinc oxide whiskers and modified manganese-doped nano-zinc sulfide and added to the energized debonding tape. The energized debonding effect and adhesion are reduced, and the debonding time is increased. This may be because the zinc oxide crystals loaded with porous carbon and the modified manganese-doped nano-zinc sulfide exist in the cross-linked network hydrogel, shortening the distance between the zinc oxide crystals loaded with porous carbon and the modified manganese-doped nano-zinc sulfide. After energization, the conductive adhesive layer loses its viscosity in a short time, and has a higher energized debonding efficiency. However, no composite conductive hydrogel is formed in Comparative Example 13, and this effect cannot be achieved. Therefore, the energized debonding effect and adhesion are reduced.

[0119] The data in Table 1 show that the electrically conductive debonding tapes prepared in Examples 4-6 meet the test performance requirements, while the electrically conductive debonding tapes prepared in Comparative Examples 9-13 do not meet the performance requirements, indicating that the electrically conductive debonding tapes prepared in the present invention have good electrically conductive debonding performance and shear strength.

[0120] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0121] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing an electrically conductive adhesive tape, characterized in that: The following steps are involved: S1. Mixing an acrylate pressure-sensitive adhesive, a UV prepolymer, a composite conductive hydrogel, a curing agent, a photoinitiator, a solvent, and a leveling agent, and stirring to obtain a conductive glue; S2. Apply the conductive glue on the upper and lower surfaces of the aluminum foil substrate, dry it at 80-100°C for 5-6 minutes to obtain a conductive adhesive layer, and attach the release film to the upper and lower surfaces of the conductive adhesive layer to obtain an electrically conductive adhesive tape; The composite conductive hydrogel is prepared by a mixed reaction of modified zinc oxide whiskers, modified manganese-doped nano zinc sulfide, carboxymethyl cellulose, acrylic acid, polyethylene glycol diacrylate and ammonium persulfate; The modified zinc oxide whisker is prepared by mixing pretreated zinc oxide whisker with a carbon precursor, carbonizing the mixture, and then reacting the mixture with a silver ammonia solution and a reducing agent. The pretreated zinc oxide whiskers are specifically prepared by the following steps: The zinc oxide whiskers were added into Tris-HCl buffer, stirred evenly, dopamine was added, stirred for 3-5 hours, filtered, washed with deionized water for 3 times, and dried in an oven at 70° C. for 10 minutes to obtain pretreated zinc oxide whiskers; The modified manganese-doped nano zinc sulfide is prepared by mixing nano zinc sulfide and manganese chloride, calcining, and then surface-modifying with a silane coupling agent.

2. The method for preparing an electrically conductive adhesive tape according to claim 1, characterized in that: The carbon precursor is selected from glucose or rice husk powder; the carbonization temperature is 750-950° C., and the carbonization time is 2-4 hours.

3. The method for preparing an electrically conductive adhesive tape according to claim 1, characterized in that: The silver ammonia solution is prepared by mixing silver nitrate, deionized water and ammonia water in a dosage ratio of (0.5-1.5) g: (8-12) mL: (0.5-1.5) mL.

4. The method for preparing an electrically conductive adhesive tape according to claim 1, characterized in that: The calcination temperature is 750-850° C., and the calcination time is 2-3 hours.

5. The method for preparing an electrically conductive adhesive tape according to claim 1, characterized in that: The molecular weight of the acrylic pressure-sensitive adhesive is 380,000-680,000, and the molecular weight distribution is 2.1-2.3; the UV prepolymer is any one of polyurethane (meth) acrylate, polyester (meth) acrylate and polyether (meth) acrylate.

6. The method for preparing an electrically conductive adhesive tape according to claim 1, characterized in that: The curing agent is selected from any one of toluene diisocyanate, diphenylmethane diisocyanate, and isophorone diisocyanate; and the solvent is selected from ethyl acetate or cyclohexane.

7. The method for preparing an electrically conductive adhesive tape according to claim 1, characterized in that: The photoinitiator is selected from any one of 2-isopropylthioxanthone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and trimethylbenzoyl-diphenylphosphine oxide; the leveling agent is selected from any one of leveling agent BYK358N, leveling agent BYK-333, and leveling agent BYK381.

8. The electrically conductive adhesive tape obtained by the preparation method according to any one of claims 1 to 7.

9. The energized de-viscosity tape prepared by the preparation method according to any one of claims 1 to 7 is used for fixing the battery pack of an electric vehicle.

Citation Information

Patent Citations

  • Preparation method of nitrogen-doped graded porous carbon material

    CN107572497A

  • Method for coating surface of matrix with silver and silvered tetrapod-shapedzinc oxidewhisker prepared by same

    CN109402613A

Cited By

  • Power-on viscosity-reducing adhesive tape capable of resisting plasticizer precipitation and preparation method of power-on viscosity-reducing adhesive tape

    CN121182435A

  • An electrically conductive reduced tack adhesive tape resistant to plasticizer extraction and method of making same

    CN121182435B